Implementasi Algoritma Genetika Untuk Penjadwalan Mata Pelajaran Pada LMS Getsmart - Lian Aga Aditya; Windha Mega PD (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
School timetabling in teaching and learning activities at educational institutions is a complicated thing if done manually. Because to arrange a schedule involves many components such as the number of teachers, classes, and the availability of time in schedule that can be used. So by analyzing this problem, a system which can help us to optimize and to automatically generate timetabling is needed.An approach to optimize timetabling process is by using Genetic Algorithm. This algorithm is a computational approach of the principle of natural selection from Charles Darwin’s theory of evolution and Mendel’s theory of inheritance.The case study of this research is taken place at LMS GETSMART which is an e-learning platform that doesn't have timetabling features yet. Through genetic algorithm method and using existing constraint data this system is able to produce the most optimal timetable based on its fitness value, since this algorithm uses combination of principle of natural selection and principle of inhertance to get the result as expected.